PENERAPAN METODE DISCOVERY UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 006 LANGGINI KABUPATEN KAMPAR - Yenni Fitra Surya (FIP Unimed, 2017)
Research background of low learning outcomes of science class V students under the mastery of 85%. The purpose of research to improve learning outcomes. This research is a classroom action research (PTK). The research was conducted in class V SDN 006 Langgini academic year 2016/2017 with total 23 students. Based on the results of the discussion and analysis concluded through the application of discovery method can improve students' science learning outcomes. Increased teacher activity is due to teachers are accustomed to using discovery methods. Student learning outcomes have increased from cycle I to cycle II. Students' learning outcomes before action averaged 57%, then on cycle I get 63%. Cycle II gets an average of 95%. Keywords: Learning Outcomes, Discovery Method, IPA